2012
DOI: 10.2174/157016212802138751
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Opiates and HIV Proteins on Neurons: The Role of Ferritin Heavy Chain and a Potential for Synergism

Abstract: Human immunodeficiency virus 1 (HIV-1) and its associated proteins can have a profound impact on the central nervous system. Co-morbid abuse of opiates, such as morphine and heroin, is often associated with rapid disease progression and greater neurological dysfunction. The mechanisms by which HIV proteins and opiates cause neuronal damage on their own and together are unclear. The emergence of ferritin heavy chain (FHC) as a negative regulator of the chemokine receptor CXCR4, a co-receptor for HIV, may prove … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 132 publications
0
11
0
Order By: Relevance
“…Additional exploration of opioid–chemokine interactions has revealed that the heavy chain subunit of the ubiquitously expressed iron-binding protein ferritin (FHC) can act as a negative regulator of CXCR4 signaling (Festa & Meucci, 2012; Pitcher et al, 2014; Sengupta et al, 2009). This interaction is somewhat unusual, as ferritin has classically been described for its ability to sequester iron and for its role in iron homeostasis (Wang, Knovich, Coffman, Torti, & Torti, 2010).…”
Section: Cxcr4 Interactions With Opioidsmentioning
confidence: 99%
“…Additional exploration of opioid–chemokine interactions has revealed that the heavy chain subunit of the ubiquitously expressed iron-binding protein ferritin (FHC) can act as a negative regulator of CXCR4 signaling (Festa & Meucci, 2012; Pitcher et al, 2014; Sengupta et al, 2009). This interaction is somewhat unusual, as ferritin has classically been described for its ability to sequester iron and for its role in iron homeostasis (Wang, Knovich, Coffman, Torti, & Torti, 2010).…”
Section: Cxcr4 Interactions With Opioidsmentioning
confidence: 99%
“…Incarcerated PLWH, particularly PWIDs, face enormous challenges accessing evidence-based HIV prevention interventions both within the criminal justice system and in the tumultuous period after release [1517]. Furthermore, they disproportionally experience comorbid neurocognitive impairment (NCI) [18], alcohol use disorders (AUDs) [19, 20], and depressive symptoms [11, 21, 22], which may negatively impact their HRQoL. Without adequate treatment, support and related prevention services, these individuals are at greater risk of relapsing to drug use and related risk behaviors, not being linked to HIV care, and not achieving sufficient viral suppression to improve their health and reduce HIV transmission [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that the function of p53 not only depends on p53 overexpression but also depends on post-translational modification including methylation, acylation, phosphorylation and ubiquitination 37 . The interaction of gp120 and CXCR4 could result in cellular oxidative damage, which consequently activated p53 and increased Apaf-1 phosphorylation that mediated neuronal apoptosis 38 39 . In this study, Bax, the bcl-2 family member, has been confirmed to be involved in p53-mediated neurotoxicity induced by gp120 in primary cultured mouse cortical neurons, and our study also showed that the neurotoxicity induced by high doses of gp120 is associated with the translocation of ASPP2 from the cytoplasm to the nucleus.…”
Section: Discussionmentioning
confidence: 99%